P211 Fungal and bacterial co-infections of the respiratory tract among patients with COVID-19 hospitalized in intensive care units. (20th September 2022) - Sarvestani, Hasti Kamali; Khansari, Mahmoud; Rafat, Zahra; Abdollahi, Alireza
Abstract: Poster session 2, September 22, 2022, 12:30 PM - 1:30 PM: Backgrounds: The pandemic of COVID-19 has created a global public health crisis. ICU patients with COVID-19 are prone to infections of bacterial and/or fungal origins due to several risk factors. Consequently, the current study was conducted to evaluate the frequency, demographic characteristics, underlying conditions, and etiologic agents of fungal and bacterial co-infections of the respiratory tract among ICU patients with COVID-19 in Iran. Materials and Methods: From May to October 2020, sputa and endotracheal aspirates were collected from ICU patients hospitalized with COVID-19 who also were suspected of bacterial and/or fungal co-infections according to inclusion criteria. The etiologic agents of bacterial co-infections were identified using the VITEK 2 identification method. For fungal identification, all samples were analyzed by direct microscopy using KOH 10% and culture. Furthermore, all isolates were subjected to the sequencing method. Results: A total of 73 lung specimens were obtained from patients who met the inclusion criteria. Of these, in 15 cases (20.54%) fungal and/or bacterial co-infections were confirmed. Males were more infected (73.33%) and all of them were between 49 and 79 years. Candida albicans ( n = 8, 61.53%) and Klebsiella pneumonia ( n = 5, 38.46%) were the most frequent etiologic agents related to fungal and bacterial co-infections, respectively. Pneumonia ( n = 15, 100%) and diabetes mellitus ( n = 8, 53.33%) were documented as the most prevalent underlying conditions. In the current study, 3 out of 15 patients (20%) died. Conclusion: The frequency of bacterial co-infections of the respiratory tract in ICU patients hospitalized with COVID-19 was relatively high. According to the results, one of the causes of death in these patients could be a secondary infection.